Akútne hemodynamické zmeny po nifedipine u starších mužov s esenciálnou hypertenziou - Schnapp, P; Dúbrava, Martin; Černák, Pavol (Vnitřní lékařství, 1990)
The authors selected from a group of 40 hypertonic patients 9 men (mean age 67 years, range 60-73 years) with reliably evaluated echocardiographic tracings without valvular defects and without impaired left ventricular kinetics. After two weeks on placebo every patients was given a single dose of 20 mg nifedipine. The echocardiographic examination, concurrently with a blood pressure reading, was made at the end of the placebo interval and 2.5 and 7 hours after nifedipine administration. As compared with placebo, nifedipine significantly reduced at each time intervals the end systolic stress of the wall and the blood pressure without accelerating the pulse rate. A significant reduction of the total vascular resistance and increased velocity of the circumferential fibre shortening occurred during the 2nd and 5th hour; the pulse pressure was diminished 5 and 7 hours after nifedipine administration. The favourable haemodynamic action of nifedipine after a single dose confirms the advantage of the preparation in elderly hypertensive patients.
Keywords: Hypertension; hypertenze; echokardiografie; lidé; nifedipin; Nifedipine; hemodynamika; Aged; Humans; senioři; Male; mužské pohlaví; Middle Aged; Hemodynamics; lidé středního věku; Echocardiography